2019
DOI: 10.23887/tscj.v1i2.20417
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pbl Bermuatan Kearifan Lokal terhadap Sikap Sosial dan Kemampuan Berpikir Kritis Matematika Siswa Kelas V di Gugus V Kecamatan Sukasada

Abstract: Penelitian ini bertujuan untuk mengetahui 1) perbedaan secara simultan sikap sosial dan kemampuan berpikir kritis matematika kelompok siswa yang mengikuti model PBL bermuatan kearifan lokal dan kelompok siswa yang mengikuti pembelajaran konvensional. 2) perbedaan sikap sosial kelompok siswa yang mengikuti model PBL bermuatan kearifan lokal dan kelompok siswa yang mengikuti pembelajaran konvensional. 3) perbedaan kemampuan berpikir kritis matematika kelompok siswa yang mengikuti model PBL bermuatan kearifan lok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
0
13
0
13
Order By: Relevance
“…The steps of Catur Pramana include pratyaksa (observing), anumana (concluding), upamana (comparing), sabda (testimony) (Kerti, 2018;. The finding is supported by (Primayanti et al, 2019) which shows that there is a significant effect of the PBL model containing local wisdom on the achievement of students' critical thinking skills. Then the research conducted by (Kumullah et al, 2018) which states that the ability to think and understand science concepts of students who apply the PBL model is higher than those taught by the conventional model.…”
Section: Resultsmentioning
confidence: 84%
“…The steps of Catur Pramana include pratyaksa (observing), anumana (concluding), upamana (comparing), sabda (testimony) (Kerti, 2018;. The finding is supported by (Primayanti et al, 2019) which shows that there is a significant effect of the PBL model containing local wisdom on the achievement of students' critical thinking skills. Then the research conducted by (Kumullah et al, 2018) which states that the ability to think and understand science concepts of students who apply the PBL model is higher than those taught by the conventional model.…”
Section: Resultsmentioning
confidence: 84%
“…Adventure games with ethno content can make students more familiar with their respective regions. The use of local advantages in learning can make it easier for teachers to invite students to be interested and focus on the learning process because it is directly related to everyday life (Aditya et al, 2019;Aryantini et al, 2018;Primayanti et al, 2019). The results of the needs analysis questionnaire on the indicators of the need for ethno-content learning media showed that 81% of students liked culturebased learning media, because 85% of students considered culture-based learning media to create a happy atmosphere, and 88% of students considered culture-based learning media to facilitate students in understand the learning material.…”
Section: Discussionmentioning
confidence: 99%
“…Tabel 1 menunjukkan bahwa enam SD Rintisan Kurikulum 2013 di Kabupaten Buleleng, nilai rata-rata dari hasil tes studi pendahuluan masih rendah. Selain itu, hasil wawancara dan observasi awal pada 7 Januari 2017 yang dilakukan di sekolah-sekolah Rintisan Kurikulum 2013 di SD Kabupaten Buleleng ditemukan masalah yang hampir sama yaitu masih rendahnya hasil belajar siswa disebabkan (Astraman, Dibia, & Mahadewi, 2017;Nur, Pujiastuti, & Rahman, 2016;Primayanti, Suarjana, & Astawan, 2019).…”
Section: Pendahuluanunclassified